POLYHERBAL PREPARATION AND COMPARATIVE STUDIES ON DIET-INDUCED HYPERLIPIDEMIA - NUZHAT QURESHI; RAGHVENDRA DUBEY; NILESH KUMAR PATHAK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this research article is to develop and evaluate polyherbal preparation and comparative studies on diet-induced hyperlipidemia. Methods: After the extraction, pharmacognostical and phytochemical screening was done. The lipid-lowering activity of polyherbal formulation (T1, T2, T3, T4, and T5) may be attributed to the phytoconstituents present such as alkaloids, carbohydrates, steroids, proteins, tannins, carbohydrates, flavonoids, phenols, glycosides, and triterpenes. In acute oral toxicity study, there were no behavioral changes seen up to 4 h and no mortality was observed up to the end of 24 h even at the maximum tested dose level of 2000 mg/kg per oral. It was considered maximum safe dose. Male and female albino rats weighing 150–200 g were used for the study. Hydroalcoholic extract of all plants was prepared having a dose of 2000 mg/kg. The doses were selected according to the Organisation for Economic Cooperation and Development guideline no. 425. The procedure was divided into two phases: Phase I (observation made on day 1) and Phase II (observed the animals for the next 14 days of drug administration). Animals received a single dose of 2000 mg/kg. After the administration of Healthcare Administration, food was withheld for 3–4 h. If the animal dies, conduct the main test to determine the LD50. The study was conducted by measuring various parameters, namely, daily feed intake (g), water intake (ml), body weight (g), lipid profile high-density lipoprotein (HDL), low-density lipoprotein (LDL), CHL level (mg/dl), and blood glucose level (mg/dl). Results: Results showed a significant decrease in blood glucose level and serum lipid profile such as total cholesterol, LDL, and increasing serum HDL level, so could be useful in the treatment of hypolipidemia. Conclusion: Polyherbal formulations (T1, T2, T3, T4, and T5) have hypoglycemic activity and significantly improve lipid profile levels in diet-induced experimental rats.